Peranan Pustakawan Terhadap Kualitas Layanan Perpustakaan di Era Digital Smp Islam Al-Ulum Terpadu - Dawi NurJannah; Makmur Syukri (Dinasti Review, 2024)
This article aims to explain the role of librarians in making the quality of library services in the digital era even better. This research uses qualitative understanding with a grounded theory approach. Data collection was carried out using interviews, observation, and documentation. Data analysis included data reduction, data presentation, and drawing conclusions. Data validity was guaranteed through credibility, transferability, dependability, and confirmability. The research results showed that: 1) an overview of the role of librarians on quality library services 2) librarian strategies in improving the quality of library services 3) constraints faced by librarians in improving the quality of library services, such as network constraints. The implication of the research is that the role of librarians is very important in improving the quality of library services, which ultimately has a positive impact on student achievement and overall school success.